Extending the job demands-resources model of work engagement : the role of demands and resources from other domains - Chen, I-Shuo (Trinity College (Dublin, Ireland). Trinity Business School, 2015)
This study aims to extend the job demands-resources model (JD-R model) of work engagement by proposing that in addition to job demands and job resources, as proposed in the existing JD-R model, non-work factors (e.g., non-work resources and demands) affect work engagement and job performance. This study adopts the family and home life (i.e., FHL) domain as an important non-work domain because it is well documented that family and home life issues constitute an important source of occupation-related problems that affect the mental and physical health and job performance of employees.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin.